2010
DOI: 10.1089/ars.2009.2989
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 1 Deficiency Attenuates Allergen-Induced Airway Inflammation by Suppressing Th2 and Th17 Cell Development

Abstract: Engagement of T cell receptor (TCR) triggers signaling pathways that mediate activation, proliferation, and differentiation of T lymphocytes. Such signaling events are mediated by reactive oxygen species (ROS), including hydrogen peroxide and lipid peroxides, both of which are reduced by glutathione peroxidase 1 (GPx1). We have now examined the role of GPx1 in the activation, differentiation, and functions of CD4(+) T helper (Th) cells. TCR stimulation increased the intracellular ROS concentration in Th cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 53 publications
5
57
1
2
Order By: Relevance
“…-/ -mice (268). When stimulated through the TCR, Gpx1-deficient T helper cells produced higher levels of ROS compared with wild-type controls, thus suggesting that Gpx1 may be required for controlling the oxidative burst once it is generated, but not for the initial generation of ROS during the oxidative burst.…”
Section: Selkmentioning
confidence: 95%
See 1 more Smart Citation
“…-/ -mice (268). When stimulated through the TCR, Gpx1-deficient T helper cells produced higher levels of ROS compared with wild-type controls, thus suggesting that Gpx1 may be required for controlling the oxidative burst once it is generated, but not for the initial generation of ROS during the oxidative burst.…”
Section: Selkmentioning
confidence: 95%
“…Further, there appears to be autoregulation of oxidative burst and activation in human T cells in that NOX2 expression is down-regulated 24 h after TCR-stimulation (268). Thus, the effects of a TCR-induced oxidative burst may be different on the fate of the T cells, depending on the source and the timing of ROS generation.…”
mentioning
confidence: 99%
“…Studies carried out on Se or GPx1-deficient T cells marked this equilibrium: compared to normal T cells, the lack of GPx1 resulted in increased interleukin-2 receptor (IL-2) expression and interferon-g (IFN-g) production (this enhances the oxidative burst), according to the action of TrxR1, whereas Se deficiency resulted in the opposite effect, according to globally reduced Se-proteins. 197,198 This picture of the redox regulation suggests that in T cells TrxRs stimulate the early TCR signalling events, whereas GPxs are devoted to limiting the extension of the inflammatory response after TCR signalling.…”
Section: Immune Defence and Inflammatory Disordersmentioning
confidence: 99%
“…These cells -depending on current ROS tissue status and expression of one of the regulatory moleculesmay differentiate in two directions: FoxP3 + Tregs (in the case of IDO expression) or TH17 (in the case of HIF-1α expression), where an advantage of differentiation in one direction results in the simultaneous inhibition of differentiation in the opposite direction [14,54,55,58,59]. These are important observations, considering the studies conducted by Faleo et al, who found that FoxP3 + Tregs may be involved in the mechanism of preventive effect of HBOT in an animal model (NOD mice) of autoimmune diabetes [21].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…The disease is caused by a genetically determined, abnormal immune response to an antigen/antigens (even in low doses), resulting in an excessive production of specific IgE antibodies, and after binding of the antigen with IgE and its "demonstration" to helper lymphocytes T -a proliferation of TH2 lymphocytes secreting proinflammatory cytokines leading in consequence to subjective symptoms (pruritus) and cutaneous lesions of varying advancement [8,11,14]. It is estimated that the disease can affect up to 20% of the population.…”
Section: Introductionmentioning
confidence: 99%